P902 Native American Mapuche ancestry is related to higher IBD risk in Chileans. (30th January 2023) - Pérez, T; Bustamante, M L; Magne, F; Travisany, D; Alvarez-Lobos, M; Hernandez-Rocha, C; Azocar, L; Aguilar, N; Espino, A; Estela, R; Escobar, S; Zazueta, A; et al.
Abstract: Background: Most genetic association studies rely on Caucasian, African and Asian individuals with inconsistent results depending on the population investigated, suggesting that genetic susceptibility to inflammatory bowel disease (IBD) may depend on interactions between ethnicity and genetic-environmental factors. Aim: To explore the contribution of genetic ancestry to IBD risk in Chileans. Aim: To explore the contribution of genetic ancestry to IBD risk in Chileans. Methods: 192 Chilean IBD patients were genotyped using Illumina's Global Screening Array. Genotype data was combined with similar information from 3147 population-based Chilean controls from a published study on gallstones, body mass index, c-reactive protein and gallbladder cancer in Chileans (Barahona et al., Hepatology 2021). The individual proportions of Aymara, African, European and Mapuche ancestry were estimated using the software ADMIXTURE (supervised estimation). Using the statistical software R version 4.2.1, we calculated the odds ratios (OR) and 95% confidence intervals (CI) for gender, as well as age and ancestry proportions grouped into quartiles using the library "epitools". Results: Table 1 shows the investigated characteristics of the study population and their association with IBD risk. For example, the 1 st and 3 rd quartiles of the proportion of Mapuche ancestry in IBD patients were 24.7% and 34.2%, respectively, and the corresponding OR was 2.30 (95%CI 1.52-3.48) for the lowest versus the highest group. Conclusion: The type and proportion of Native American ancestry in Chileans seems to be associated with IBD risk.